2013
DOI: 10.1111/jofi.12028
|View full text |Cite
|
Sign up to set email alerts
|

How Wise Are Crowds? Insights from Retail Orders and Stock Returns

Abstract: We analyze the role of retail investors in stock pricing using a database uniquely suited for this purpose. The data allow us to address selection bias concerns and to separately examine aggressive (market) and passive (limit) orders. Both aggressive and passive net buying positively predict firms’ monthly stock returns with no evidence of return reversal. Only aggressive orders correctly predict firm news, including earnings surprises, suggesting they convey novel cash flow information. Only passive net buyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
115
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 387 publications
(127 citation statements)
references
References 67 publications
(132 reference statements)
11
115
1
Order By: Relevance
“…The positive relationship between individual investors and PIN seems puzzling because the former have been regarded as uninformed traders due to behavioral biases (Barber and Odean, 2000), noise trading (Foucault et al, 2011) and the lack of information advantage about local stocks (Seasholes and Zhu, 2010). However, there is growing empirical evidence that individual investors possess valuable private information and engage in informed trading (Kelley and Tetlock, 2013;Fong et al, 2014a;Tian et al, 2015). This possibility of individuals having private information cannot be ruled out in the context of Malaysia, given the prevalence of ownership concentration in the hands of family (see Carney and Child, 2013).…”
Section: Estimation Results and Discussionmentioning
confidence: 99%
“…The positive relationship between individual investors and PIN seems puzzling because the former have been regarded as uninformed traders due to behavioral biases (Barber and Odean, 2000), noise trading (Foucault et al, 2011) and the lack of information advantage about local stocks (Seasholes and Zhu, 2010). However, there is growing empirical evidence that individual investors possess valuable private information and engage in informed trading (Kelley and Tetlock, 2013;Fong et al, 2014a;Tian et al, 2015). This possibility of individuals having private information cannot be ruled out in the context of Malaysia, given the prevalence of ownership concentration in the hands of family (see Carney and Child, 2013).…”
Section: Estimation Results and Discussionmentioning
confidence: 99%
“…Previous research shows that the tone in newspaper columns drives investor sentiment (Tetlock, 2007;Garcia, 2013), captures information beyond fundamentals (Tetlock, Saar-Tsechansky, and Macskassy, 2008) and affects individual trading behaviour (Kelley and Tetlock, 2013). Moreover, the tone of news can be improved by increasing local advertising spending (Gurun and Butler, 2012) and hiring investor relationship firms (Solomon, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…S ince Galton's discovery of the "wisdom of crowds" over 100 years ago (1), results on crowdsourcing (1, 2), prediction markets (3), and financial forecasting (4,5) have shown that the aggregated judgment of many individuals can be more accurate than the judgments of individual experts (2,4,(6)(7)(8). Statistical explanations for this phenomenon argue that group accuracy relies on estimates taken from groups where individuals' errors are either uncorrelated or negatively correlated, thereby preserving the diversity of opinions in a population (9).…”
mentioning
confidence: 99%